1970
DOI: 10.1128/jb.104.1.323-330.1970
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Membrane Lipid Composition in Exponentially Growing Staphylococcus aureus During the Shift from 37 to 25 C

Abstract: Lowering the temperature of growth of Staphylococcus aureus from 37 to 25 C decreased the growth rate and induced changes in the composition of the membrane lipids. Changes in lipid composition also occur in the transition between exponential and stationary growth phases at one temperature. To isolate the effects of lowering the temperature, exponentially growing S. aureus was abruptly switched from 37 to 25 C by transfer to cooler medium. Exponential growth continued at 25 C without a lag period but with a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 36 publications
2
31
1
Order By: Relevance
“…There were statistically significant differences between the cellular fatty acid compositions of the groups in terms of Cil5 = 0 and C20 = 0. The cellular fatty acids of all the strains tested were saturated rather than unsaturated (13,20,22). The quantitative differences found between the fatty acid components in the present and earlier taxonomic studies on S. aureus (6,28) may be attributable to differences in cultivation conditions (24,25).…”
Section: Discussioncontrasting
confidence: 43%
“…There were statistically significant differences between the cellular fatty acid compositions of the groups in terms of Cil5 = 0 and C20 = 0. The cellular fatty acids of all the strains tested were saturated rather than unsaturated (13,20,22). The quantitative differences found between the fatty acid components in the present and earlier taxonomic studies on S. aureus (6,28) may be attributable to differences in cultivation conditions (24,25).…”
Section: Discussioncontrasting
confidence: 43%
“…We also observed such a trend in our samples, but there were no significant differences at a ¼ 0:05. Nevertheless, it should be noted that some reports have indicated that several bacterial strains do not display this shift [40,41], and that other changes, e.g., from 16:1x7c to cy17:0 may also be possible [42]. Accordingly, even though it is known that methanotrophs, like other bacteria, can alter the composition of their membranes in response to changes in temperature, the increases in the methanotroph-associated PLFAs in our samples were probably caused by a rise in biomass, since the kinetics of CH 4 consumption were consistent with the growth of CH 4 oxidisers.…”
Section: Discussionmentioning
confidence: 90%
“…The FabH preference for 2-methylbutyryl-CoA at 10 1C supports the idea that FabH substrate specificity contributes to the increased proportion of anteiso fatty acids produced by bacteria during cold adaptation. We think that these basic observations on substrate specificity will also apply to the FabH enzymes of other bacteria that increase the content of anteiso fatty acids at lower growth temperatures, such as B. subtilis (Klein et al, 1999), S. aureus (Joyce et al, 1970), and other Gram-positive bacteria (Suutari & Laakso, 1994).…”
Section: Intracellular Acyl-coa Pools In L Monocytogenesmentioning
confidence: 90%